Race and Stereotypes Matter When You Ask About Conduct Problems: Implications for Violence Risk Assessment in Juvenile Justice Settings. (January 2019) - Andretta, James R.; Worrell, Frank C.; Watkins, Katara M.; Sutton, Ryan M.; Thompson, Adrian D.; Woodland, Malcolm H.
We examined the impact of stigma priming on self-reported severe conduct problems in two studies conducted with African American adolescents involved in the juvenile justice system. Data-collection interviews were conducted in a secure detention setting following arrest. In Study 1 ( N = 193), stigma was primed by manipulating the ordering of surveys. Adolescents who completed a questionnaire about racial identity attitudes prior to questions about severe conduct reported substantively more problematic behaviors than control group peers (β = 0.43). In Study 2 ( N = 264), stigma was primed by manipulating whether adolescents were interviewed by an African American or European American mental health professional. Racial group membership of the interviewer did not have a substantial effect on self-reported conduct problems (β = −0.04). Although the studies were not without limitations, they highlight the need for more research on the degree to which interview methods and context influence self-reported severe conduct behavior in forensic settings.